The role of demography and climatic events in shaping the phylogeography of Amazona aestiva (Psittaciformes, Aves) and definition of management units for conservation - Caparroz, Renato (2009)
Aim: The blue‐fronted amazon (Amazona aestiva) is a widely distributed Neotropical parrot with two recognized sub‐species, which are mainly characterized by the colour of the shoulder. We explored mitochondrial DNA variability to determine how demographic processes and historical climatic fluctuations may have contributed to phylogeographical pattern and morphological variation of A. aestiva, and how this information could be useful to understand the evolutionary relationship of this species and the Amazona ochrocephala complex and to determine management units for conservation purposes. Location: Brazil and north‐eastern Argentina. Methods: We analysed a fragment of COI gene of 78 A. aestiva and 27 A. ochrocephala. We computed a median‐joining network, and the population structure of A. aestiva populations was assessed using a hierarchical analysis of nucleotide diversity. The mismatch distribution, Fu's Fs‐test of neutrality and R2 test were used to detect past population expansion. Results: All A. aestiva haplotypes and A. ochrocephala subspecies from north‐eastern and southern South America were recovered within the South American clade. Hierarchical analysis of nucleotide diversity of A. aestiva populations detected two geographical groups as obtained by median‐joining network. These two A. aestiva groups showed evidence of a recent population expansion. The time of populations splitting estimated corresponding to the Middle Pleistocene. Main conclusions: The two A. aestiva genetic groups identified in our analyses agree with the morphological variation, corresponding to named subspecies. These two A. aestiva groups have undergone a recent population expansion, with low gene flow between them. The expansion of savannah areas may have contributed to the population expansion of these two groups. We concluded that introgression after isolated diversification may better explain haplotype sharing between A. aestiva and A. ochrocephala subspecies. We suggest that management and conservation strategies should consider these two A. aestiva groups (or subspecies) as different management units and should maintain viable populations of these two management units.